Synthesis of Pyrrolo[1,2-a]indoles via (3+2)-Annulations of (Aza)-para-Quinone Methides with Indoles - Zhang, Xiang-Zhi; Qiu, Zong-Wang; Wen, Gui-Hua; Ma, Ai-Jun; Bao, Peng-Jin; Du, Ji-Yuan; Xu, Xue-Tao; Feng, Na; Li, Bao Qiong (Synthesis, 2020)
An efficient and straightforward Brønsted acid mediated (3+2)-annulation of (aza)-para-quinone methides, generated in situ from propargylic alcohols and indoles, has been developed involving 1,8-conjugate addition/5-endo annulation cascade. This protocol affords a mild and effective method for the construction of synthetically important and structurally interesting functionalized pyrrolo[1,2-a]indoles.
Keywords: para-quinone methides; para-quinone methide imines; 1,8-conjugate addition; [3+2] annulation; pyrrolo[1,2-a]indoles